Analisis Bahan Kimia Obat dalam Sediaan Jamu Pegal Linu dengan Metode KLT dan Spektrofotometri Uv-Vis - Ita Handayani; Ratih Tyas Widara; Fendi Yoga Wardana; Carmenita Maharani Aditiya (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
One of the traditional medicines widely consumed by the Indonesian people is herbal medicine for aches and pains with the requirement that it should not contain medicinal chemicals. Paracetamol, ibuprofen, and mefenamic acid are medicinal chemicals that are often added to herbal medicine for aches and pains. The purpose of this study was to determine the content and levels of paracetamol, ibuprofen, and mefenamic acid in herbal medicine for aches and pains circulating in Batu City. The samples used were 10 herbal medicine for aches and pains both branded and unbranded circulating in Batu City. The content of medicinal chemicals was identified qualitatively by KLT test method with stationary phase used GF254 and mobile phase chloroform: ethanol (9:1), chloroform: methanol (8:1), and ethyl acetate: methanol: ammonia (85:10:5), as well as color reaction test (FeCl3, methyl red, and vitali morin). Meanwhile, quantitative tests were carried out using the UV-Vis spectrophotometric method. The results of qualitative analysis with KLT there are 3 samples that can be seen in UV light 254 nm, namely SJ2, SJ3, and SJ5. In the color reaction test with FeCl3 reagent there was 1 positive sample, namely SJ3, methyl red reagent with all samples showing positive results except SJ6, and for vitali morin reagent only SJ2 was positive. The results of quantitative analysis by UV-Vis spectrophotometry showed that all samples contained BKO (paracetamol, ibuprofen, and mefenamic acid). The highest concentration of BKO was found in SJ2 (PCT 5.31%, IP 12%, and AM 5.75%) and SJ3 (PCT 5.33%, IP 14.8%, and AM 4.45%).